Family functioning and child behavioral problems with Duchenne/Becker muscular dystrophy: A cross-sectional study - Turan, Serkan; Ülgenalp, Ayfer; Memiş, Hande; Yiş, Uluç; Akay Pekcanlar, Aynur (Journal of Surgery and Medicine, 2019)
Aim: Duchenne/Becker muscular dystrophy (DBMD) in children is associated with emotional and behavioral problems and impairment at family functioning. The current study aimed to explicate family functioning and child behavioral problems with DBMD. Methods: The study involved 28 child and adolescents with DBMD attending Dokuz Eylul University Medical Genetics and Child and Adolescent Psychiatry Outpatient Clinic from January 2019 to March 2019 and comprised 50 healthy control subjects. The participants who were evaluated with Kiddie-Sads-Present and Lifetime (K-SADS-PL) by blinded professionals completed a data form containing questions regarding sociodemographic and clinical features, Wechsler Intelligence Scale for Children-Revised (WISC-R) (for only DBMD cases), the Beck Depression Scale (BDS), State-Trait Anxiety Inventory (STAI), Parenteral Attitude Research Instrument (PARI), the Child Behavior Checklist (CBCL) and Family Assessment Device. Results: Mothers of the children with DBMD demonstrated higher scores in Beck Depression Inventory and State-Trait Anxiety Inventory scales, which is associated with anxious and depressive states as compared with those from the control group but not statistically significant (P=0.888, P=0.584 and P=0.646, respectively). DBMD cases demonstrated significantly higher scores in most of the Child Behavior Checklist (activities, withdrawn/depressed, somatic complaints etc.), meaning that they have many problem areas affecting family functioning and the quality of life of the patient (P<0.001). Conclusion: This study demonstrated that, for parents who have children with DBMD, DBMD had a negative effect on their lives, and their family relationships. However, further studies with larger sample sizes are required to reach stronger conclusions.